The roles of the instructors in an ESP-task based language teaching course - Vargas Vásquez, José Miguel; Moya Chaves, Maciel; Garro Morales, Carolina (Actualidades Investigativas en Educación, 2016)
The graduate program in Teaching English at the University of Costa Rica offers yearly English courses to satisfy the language learning needs at different departments, research centers, or similar institutions. The objective of this article was to analyze the extent to which a group of student teachers fulfilled the roles of the instructors in the Task Based Language Teaching method used in the graduate program. The study used a mixed-methods approach and the subjects were three instructors during their teaching practicum. The roles of the instructors were assessed by the practicum supervisors, fellow students in the practicum, the students in the course, and the instructors themselves through rubrics, observation sheets, surveys, and teaching journals. The results from the different instruments using different scales pointed to the instructors fulfilling the roles of sequencing tasks and motivating the learners a majority of the times. The roles of preparing the learners for tasks and raising consciousness were fulfilled to a lesser extent, which indicated that the instructors needed to work further on these areas. The study concluded with recommendations for improving the roles that revealed weaknesses, notably aimed to provide a manageable numbers of vocabulary items and grammar structures in the pretask, as well as to provide prompt feedback, and to elicit students’ knowledge for the development of lessons.